Culture and the labour market - Austen, Siobhan (E. Elgar Pub., 2003)
"Culture and the Labour Market attempts to define the meaning of culture and the nature of its possible consequences on economic processes and outcomes. In particular, the book examines alternative theoretical and empirical approaches to the economic analysis of cultural effects in the labour market. Using extensive new data from fourteen countries, the author finds tangible evidence of substantial cross-cultural differences in beliefs about wage inequality." "This study of the economic influence of culture will be indispensable to labour and social economists. It will also be of value to academics working on labour market theory and policy, and the hitherto neglected link with culture."--BOOK JACKET.